Single‐Cell Landscape Highlights Heterogenous Microenvironment, Novel Immune Reaction Patterns, Potential Biomarkers and Unique Therapeutic Strategies of Cervical Squamous Carcinoma, Human Papillomavirus‐Associated (HPVA) and Non‐HPVA Adenocarcinoma. Issue 10 (1st February 2023) - Qiu, Junjun; Qu, Xinyu; Wang, Yumeng; Guo, Chenyan; Lv, Bin; Jiang, Qian; Su, Wentao; Wang, Li; Hua, Keqin
Abstract: Cervical adenocarcinomas (ADCs), including human papillomavirus (HPV)‐associated (HPVA) and non‐HPVA (NHPVA), though exhibiting a more malignant phenotype and poorer prognosis, are treated identically to squamous cell carcinoma (SCC). This clinical dilemma requires a deeper investigation into their differences. Herein a transcriptomic atlas of SCC, HPVA, and NHPVA‐ADC using single‐cell RNA (scRNA) and T‐cell receptor sequencing (TCR‐seq) is presented. Regarding structural cells, the malignancy origin of epithelial cells, angiogenic tip cells and two subtypes of fibroblasts is revealed. The promalignant properties of the structural cells using organoids are further confirmed. Regarding immune cells, myeloid cells with multiple functions other than antigen presentation and exhausted T lymphocytes contribute to immunosuppression. From the perspective of HPV infection, not only is HPV‐dependent and independent cervical cancer oncogenesis proposed but also three immune reaction patterns mediated by T cells (coordinated/inactive/imbalanced) are identified. Strikingly, diagnostic biomarkers to distinguish ADC from SCC are discovered and prognostic biomarkers with marker genes for malignant epithelial cells, tip cells, and SPP1/C1QC macrophages are generated. Importantly, the efficacy of anti‐CD96 and anti‐TIGIT, not inferior to anti‐PD1, in animal experiments is confirmed and targeted therapies specifically for HPV‐positive SCC, HPVA and NHPVA‐ADC, providing essential clues for further clinical trials, are proposed. Abstract : A comprehensive single‐cell atlas of cervical cancer (CC), including HPV‐positive squamous cell carcinoma (SCC), HPV associated (HPVA) and non‐HPV associated (NHPVA) adenocarcinoma, is depicted. Through verification from organoid culture, mice experiments and clinical samples, the complex CC microenvironment is unveiled, novel clinical biomarkers are generated, and promising precise treatment modalities are proposed, providing essential clues for further CC clinical trials.